(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2013)
The axial heat conduction in parallel flow microchannel heat exchanger with rectangular ducts was numerically investigated, for laminar, 3-D, incompressible, and steady state flow of water. The governing equations, continuity, Navier-Stokes equations (momentum equations), and the energy equations for the hot and cold fluids were solved by using SIMPLE algorithm with finite volume method and FORTRAN code to obtain the temperature distribution for the two fluids and the separating wall between them. The results play an important role of the axial heat conduction on the effectiveness in parallel flow microchannel heat exchanger and the factors affecting the axial heat conduction are; Reynolds number Re, thermal conductivity ratio, aspect ratio ? and channel volume. Increasing of Re, , ? and channel volume each separately leads to increase the axial heat conduction and vice versa.